2021
DOI: 10.1061/(asce)me.1943-5479.0000902
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Differences in Underrepresented Civil Engineering Students’ Career Satisfaction Expectations and College Experiences

Abstract: Student career satisfaction expectations and college experiences are an underutilized map toward attracting and sustaining the interest of underrepresented groups (URGs) in the civil engineering and construction industry. URGs provide indispensable contributions to the development of the built environment; however, URGs in civil engineering have not received sufficient attention to their unique expectations and experiences. Furthermore, diversity and inclusion efforts still are special practices in civil engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(67 reference statements)
0
5
0
1
Order By: Relevance
“…This finding implies out-of-class activities are important to civil engineering undergraduate students from underrepresented groups. Keku et al (2021) identified the differences in civil engineering and construction undergraduate students' career satisfaction expectations and participation in cocurricular activities (i.e., participation in an organization for women and minorities in engineering and an outreach club) between underrepresented and non-underrepresented groups. Hamlet et al (2021) found that upper-division female students in civil and construction engineering education programs have a more robust engineering identity than their counterparts, and highlighted the importance of building and sustaining a female's strong engineering identity.…”
Section: Underrepresented Groups In Engineering-construction Education Programsmentioning
confidence: 99%
“…This finding implies out-of-class activities are important to civil engineering undergraduate students from underrepresented groups. Keku et al (2021) identified the differences in civil engineering and construction undergraduate students' career satisfaction expectations and participation in cocurricular activities (i.e., participation in an organization for women and minorities in engineering and an outreach club) between underrepresented and non-underrepresented groups. Hamlet et al (2021) found that upper-division female students in civil and construction engineering education programs have a more robust engineering identity than their counterparts, and highlighted the importance of building and sustaining a female's strong engineering identity.…”
Section: Underrepresented Groups In Engineering-construction Education Programsmentioning
confidence: 99%
“…Our preliminary search yielded 107 articles from 47 different sources. (15) appeared in the proceedings of either FIE or the ASEE Annual Conference, and as with the full set of articles, about three quarters were published from 2017 to the present.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…The subset we focus on in this paper comprises 31 articles from 17 different sources (Table 4), from the years 1996 to 2021. Almost half of these articles (15) appeared in the proceedings of either FIE or the ASEE Annual Conference, and as with the full set of articles, about three quarters were published from 2017 to the present.…”
Section: Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como señala Spertus (1991), la desigualdad en la educación hacia los/as niños/as, transmitiendo valores diferentes de acuerdo con el género, así como la expresión sutil o directa de estereotipos y sesgos sobre estas disciplinas, llevan a áreas STEM a verse afectadas por la segregación, especialmente, los campos de la informática y la ingeniería. El sector educativo STEM padece de baja representación de diversidad de género, especialmente, de mujeres (Jacobs et al, 2017), y de forma notable esta baja representación se produce en el sector de la ingeniería La brecha de género en los estudios universitarios del sector STEM en el espacio español de educación | Sonia Verdugo Castro (Cvencek et al, 2021;Dou et al, 2020;Keku et al, 2021;Moote et al, 2020;Snyder et al, 2018). Debido a la importancia de las influencias sociales y el impacto del contexto y entorno sobre las decisiones de la persona, se considera necesario profundizar en los factores que intervienen en el proceso.…”
Section: Brecha De Género En El Sector Stemunclassified